Examining the relationship between veterinarians and veterinary physiotherapists in South Africa post registration of the veterinary physiotherapy profession - Louw, Amy (Department of Health and Rehabilitation Sciences, 2026)
Background: Veterinary physiotherapy is a newly promulgated independent profession in South Africa. Veterinary physiotherapists need to work under referral or in collaboration with a veterinarian. A multidisciplinary approach to patient management is beneficial. It is therefore essential to determine the current perception of the veterinary physiotherapy profession by veterinarians. Aims and Objectives: This study aimed to explore the dynamics of the relationship between veterinarians and veterinary physiotherapists, particularly post-promulgation of the veterinary physiotherapy profession. It further aimed to identify the barriers and facilitators to referrals from veterinarians to ensure integration of the profession. Methods: This was a descriptive cross-sectional study that used a mixed method approach. The study population included veterinarians and veterinary physiotherapists registered or authorised with the South African Veterinary Council (SAVC). Three phases of data collection were completed – the qualitative components were covered in phase one and three of data collection through interviews. Four interview participants were specifically selected for the first phase based on their expertise and knowledge of their respective professions. Six interview candidates volunteered for the third phase of data collection, three veterinarians and three veterinary physiotherapists. The quantitative component was derived from phase two, through the questionnaire results. Sample size for the questionnaires were calculated using population numbers provided by the South African Veterinary Association and the South African Physical Rehabilitation for Animals Association, both of which were utilised for the distribution of the questionnaires. Data Analysis: Qualitative data from the interviews was analysed using an inductive thematic approach to identify common themes. Data from the questionnaires was analysed using a descriptive analysis, and correlation tests were conducted to determine the relationship between variables. Statistical significance was calculated and determined using p < 0.05. i Results: The questionnaires were completed by 97 veterinarians and 59 veterinary physiotherapists respectively. Eighty-two percent (n = 80) of veterinarians were aware of the promulgation of the veterinary physiotherapy profession, while 65% (n = 63) of the veterinarians referred patients to veterinary physiotherapy regularly. Significant correlations were found between the type of veterinary practice and the likelihood to refer to veterinary physiotherapy. Forty-nine percent (n = 29) of veterinary physiotherapists receive regular referrals from veterinarians. There was a significant correlation between regular referrals from veterinarians and a higher veterinary physiotherapy caseload. The type of physiotherapy practice was found to significantly correlate with the referrals received. The interviews revealed themes around how communication, location, and understanding of the physiotherapy profession impacted the veterinarian's likelihood to refer. All participants felt that the promulgation was a positive step forward for the veterinary physiotherapy profession. Conclusion: Overall, there appears to be a positive perception of the veterinary physiotherapy profession from veterinarians. However, there is considerable room for growth with regards to veterinary referrals to veterinary physiotherapy. Most participants are happy about the promulgation of the profession and feel that it will assist with the growth of the profession. Recommendations to ensure integration of the veterinary physiotherapy profession into the veterinary field include improving communication between the practitioners, improving promotion of local veterinary physiotherapy practices, and education regarding the scope and function of veterinary physiotherapy profession to veterinarians and the public. Keywords Veterinary Physiotherapy; Veterinarians; Promulgation; Veterinary multidisciplinary team.